Models and Theories : A Philosophical Inquiry. - Frigg, Roman. (Taylor & Francis Group, 2022)
An accessible yet critical introduction to the debates about models and theories within analytical philosophy of science since the 1920s. Essential reading for advanced undergraduates and researchers working in philosophy of science, philosophy of mathematics, and philosophy of technology.